CUSTOMER RELATIONSHIP MANAGEMENT THROUGH MAINTENANCE REMINDER APPOITMENT ON MANYAR AUTO2000 WORKSHOP - Safitri, Indah; Sukaris (Mount Hope Economic Global Journal, 2024)
In this study, the strategy used by MRA employees is to build communication via telephone, by reminding customers about routine services carried out every six months, offering service bookings, informing promos and benefits provided if customers perform routine service at authorized workshops, the conclusion is that by doing customer relationship management appropriately via telephone is proven to create good service quality and increased customer loyalty. The purpose of this study focuses on after-sales service, namely the role of MRA employees who are tasked with creating customer loyalty so that they can increase unit entry by reminding customer service schedules and strategies for building communication relationships with customers via telephone. This research is descriptive research with qualitative methods. The subject of this research is Maintenance Reminder Appoitment employees, valley, primary data collection using interview and observation techniques.